2023
DOI: 10.1097/jfn.0000000000000420
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Presentations of Strangulation in Intimate Partner Violence Relationships

Abstract: Patients presenting to the emergency department after strangulation are in need of specialized care and treatment. Patient presentations after nonfatal strangulations vary dramatically; however, regardless of variation, no assumptions should be made about the seriousness of the injury. The clinician's goal should be a thorough assessment and evaluation, followed by treatment in accordance with individual patient needs. One way to ensure this comprehensive care is through the implementation of forensic nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…The experimental model ultimately concluded that the amount of force applied, irrespective of the victim's attempts at self-defense, exceeded 5 kg, and was enough to cause blood vessels in the neck to constrict [ 10 - 14 ]. These findings were presented in Court as scientific evidence that the manner and force of the strangulation were indeed consistent with an attempted murder [ 15 - 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental model ultimately concluded that the amount of force applied, irrespective of the victim's attempts at self-defense, exceeded 5 kg, and was enough to cause blood vessels in the neck to constrict [ 10 - 14 ]. These findings were presented in Court as scientific evidence that the manner and force of the strangulation were indeed consistent with an attempted murder [ 15 - 16 ].…”
Section: Discussionmentioning
confidence: 99%